2016
DOI: 10.1039/c6nr02051h
|View full text |Cite
|
Sign up to set email alerts
|

MD simulation study of direct permeation of a nanoparticle across the cell membrane under an external electric field

Abstract: Nanoparticles (NPs) have been attracting much attention for biomedical and pharmaceutical applications. In most of the applications, NPs are required to translocate across the cell membrane and to reach the cell cytosol. Experimental studies have reported that by applying an electric field NPs can directly permeate across the cell membrane without the confinement of NPs by endocytic vesicles. However, damage to the cell can often be a concern. Understanding of the mechanism underlying the direct permeation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 45 publications
2
65
0
Order By: Relevance
“…These unbiased MD simulations demonstrated that when some additional settings are adopted, an NP can directly permeate across a lipid bilayer. So far, the following special settings have been found to induce the NP direct permeation: the reversible reaction between NP and ligands (Ding et al, 2012), multiple NPs , application of an external electric field (Shimizu et al, 2016). Ding et al (2012) proposed a new type of ligand-coated NP and demonstrated that their NP can directly permeate across a lipid bilayer (Fig.…”
Section: Unbiased MD Simulation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These unbiased MD simulations demonstrated that when some additional settings are adopted, an NP can directly permeate across a lipid bilayer. So far, the following special settings have been found to induce the NP direct permeation: the reversible reaction between NP and ligands (Ding et al, 2012), multiple NPs , application of an external electric field (Shimizu et al, 2016). Ding et al (2012) proposed a new type of ligand-coated NP and demonstrated that their NP can directly permeate across a lipid bilayer (Fig.…”
Section: Unbiased MD Simulation Studiesmentioning
confidence: 99%
“…As reviewed in Section 3, application of external force fields can be an effective way to directly deliver NPs into a cell, although its mechanism is largely unknown. We focused on the electroporation-assisted NP delivery and investigated for the first time the NP permeation across a lipid bilayer under an external electric field by means of an unbiased MD simulation (Shimizu et al, 2016). We used an alkanethiol-coated cationic gold nanoparticle with 4 nm diameter for the simulation.…”
Section: Unbiased MD Simulation Studiesmentioning
confidence: 99%
“…The resealing of plasma membrane pores after electroporation is a requisite for cell survival . Membrane resealing is closely related to plasma membrane fluidity, which plays important roles in many biological processes and signaling .…”
mentioning
confidence: 99%
“…The NPs–membrane interaction behaviors a) without external force and electric field, b) with external force on NP, c) with a low electric field, d) with excessive applied membrane potential, which is equal to the membrane breakdown intensity. Reproduced with permission . Copyright 2016, Royal Society of Chemistry.…”
Section: Modeling and Simulation Of Ncs Delivery Through Biological Bmentioning
confidence: 99%